Industry Structure with Fluctuating Demand - Mills, David E.; Schumann, Laurence (American Economic Review, 2016)
The intra-industry distribution of demandinduced output fluctuations is a neglected aspect of the theory of industrial organization. The standard model of competitive equilibrium has identical firms and stationary demand. Eytan Sheshinski and Jacques Dreze (1976) extended this model to an environment with demand fluctuations to study its industry-structure implications. They concluded that demand fluctuations increase the number of firms sustained in competitive equilibrium, and that each firm produces less on average with fluctuations than without. By preserving the identical-firm assumption, Sheshinski and Dreze predict that industrywide output fluctuations are distributed equally among competitors. An alternative model of competitive equilibrium with stationary demand would have constant-returns-to-scale firms with various output levels. Such firms would be proportionate clones of each other in a technological sense. The analagous extension of this model to an environment with demand